Reflection reinforces effectiveness of analyses of potential Results of the Intervention Study (ISPA) - Kunert, Carolin [Verfasser]; Sommer, Jörn [Verfasser] (My University, 2023)
Analyses of potential have formed a separate part of the Vocational Orientation Programme of the Federal Ministry of Education and Research (BMBF) since 2010. Various ways of conducting an analysis of potential have developed over the course of time and in the wake of federal state-specific adjustments. The effectiveness of different approaches has now been investigated in an Intervention Study (ISPA) commissioned by the BMBF. This article presents the background to the study and its main results.
Keywords: L 5 Beratung & Orientierung; 370; Berufsorientierung; Programm; Berufswahl; Kompetenzfeststellung